The biopic genre in contemporary culture as a marker of a new style - Автухович, Татьяна (Вопросы семантики и стилистики текста: лингвистический дискурс, 2021)
The article raises the question of socio-cultural changes and the emergence of the term biopic. It is argued that biopic is a marker of a new style and can refer to modern culture as a whole. On the basis of a brief study of the history of the genre and analysis of examples of biopic in the cinema and literature, it is concluded that, unlike traditional biographies, the purpose of which is to adopt the ideas of conceptualization of life in accordance with the public interest standard and, in this regard, the correlation of biography with a historical context, biopic follows a different model of presenting biographical material (it is not the protagonist’s achievements but his or her private life that comes to the fore; it is not his or her conscious pursuit of life goals but accidental success as the result of a game of chance and circumstances).